Cultural diversity in LIS research: National and international communities as context for the study of ethics, policy, and education. Issue 1 (24th February 2016) - Agosto, Denise; Zhang, Bella Jing; Unsworth, Kristene; Bossaller, Jenny; Turner, Deborah
ABSTRACT: This panel will showcase current information ethics, information policy, and library and information science (LIS) education projects from around the world to compare and contrast the current state of LIS research in the global information community. The juxtaposition of selected international projects will highlight the roles that national and international cultural contexts can play in LIS research, policy, and practice.